Peasant Metropolis : Social Identities in Moscow, 1929-1941 - Hoffmann, David L. (David Lloyd), 1961- (Book collections on Project MUSE., 1994)
The conservative and coercive policies that Party leaders adopted in response, he argues, contributed to the Soviet Union's emergence as an authoritarian welfare state.